Data Troubles: Digital Distribution in the Platform Economy - Holt, Jennifer; Justus Liebig University Giessen (My University, 2019)
This essay examines the distribution of content in the global market and how it has become imbricated with cloud policy through online platforms, remote data storage, and the patchwork of international laws, Terms of Service agreements, and policies currently regulating the 1s and 0s being stored and streamed as digital media. Distributing and protecting digital data as it travels all over the world poses challenges that often defy legal paradigms, national boundaries, and traditional geographies of control. Moreover, the incursion of platforms and other intermediaries into the digital distribution landscape has created challenges for everyone from tech companies and theater owners to regulators and audiences. Looking at some of the industrial, cultural, and political dynamics connecting the governance of data with the shifting realities of digital distribution, I will address the growing data troubles faced by the media industries and relate them to the growing stakes for the futures of culture, information, and citizenship in the platform era.
Keywords: digital distribution; platforms; data; cloud; policy; streaming; ddc:300